Hormonal and genetic basis of sexual differentiation disorders and hot topics in endocrinology proceedings of the 2nd world conference - New, Maria I. 1928-; Simpson, Joe Leigh 1943- (Advances in experimental medicine and biology, 2011)
Proceedings of the 2nd World Conference? Hormonal and Genetic Basis of Sexual Differentiation Disorders and Hot Topics in Endocrinology. The meeting took place at The Eden Roc Hotel in Miami Beach, Florida, 1/15/10 ? 1/17-10. Endocrinology and more specifically, the area of sexual differentiation disorders is an evolving field of medicine. The diagnosis and treatment of Disorders of Sex Development (DSD) is multi-faceted.